2007
DOI: 10.1097/mbc.0b013e3281139c34
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin activatable fibrinolysis inhibitor and its relationship to fibrinolysis and inflammation during the acute and convalescent phase of ischemic stroke

Abstract: To investigate thrombin activatable fibrinolysis inhibitor (TAFI) in ischemic stroke and its relationship to fibrinolysis and inflammation, we investigated 32 patients with ischemic stroke during the acute phase and after 60 days. TAFI antigen levels, global markers of hemostasis (coagulation and fibrinolysis) and inflammatory markers were measured in plasma. TAFI antigen levels were significantly elevated at admission (128%; 109-151%) and at day 1 (129%; 109-152%) compared with day 60 (108%; 91-127%; both P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
(37 reference statements)
4
27
0
Order By: Relevance
“…Previous studies on proCPU plasma concentration in an acute ischemic stroke population reported higher proCPU levels in stroke patients in comparison with controls [24,25]. In our present study, mean proCPU levels at admission of the total stroke population amounted to 966 ± 179 U L )1 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies on proCPU plasma concentration in an acute ischemic stroke population reported higher proCPU levels in stroke patients in comparison with controls [24,25]. In our present study, mean proCPU levels at admission of the total stroke population amounted to 966 ± 179 U L )1 .…”
Section: Discussionsupporting
confidence: 56%
“…Several epidemiological studies demonstrated that plasma proCPU concentrations are related to thrombotic tendency [19,20]. Association between plasma proCPU levels and the occurrence of ischemic stroke was reported in a number of clinical studies [21][22][23][24][25]. Recently, we demonstrated in patients with ischemic stroke receiving thrombolytic therapy, that activation of the proCPU system takes place and results in measurable amounts of CPU in the circulation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this observation, TAFI and PAI-1 levels are increased in patients suffering from ischemic stroke, often correlating with stroke severity, suggesting a negative impact of these antifibrinolytic molecules in stroke development. 8,[44][45][46][47][48][49][50] Interestingly, whereas the diabody ameliorated the outcome in this model, tPA has a controversial effect, potentially through aggravating neuronal damage after focal cerebral ischemia. 51 As a control, an in vitro neurotoxicity assay was performed with or without N-methyl-D-aspartate and demonstrated the absence of any neurotoxicity associated with the diabody (supplemental Figure 4).…”
Section: Blood 19 February 2015 X Volume 125 Number 8 Dual Tafi/paimentioning
confidence: 99%
“…The thrombin-activatable fibrinolysis inhibitor (TAFI), an enzyme that may act as a link between coagulation and fibrinolysis, inhibits fibrinolysis by removing carboxyterminal residues from partially degraded fibrin, thus decreasing plasminogen binding on the surface of fibrin [15,16]. Increased TAFI levels have been associated with several thrombotic conditions like venous thromboembolism [17,18] and ischemic stroke [19,20].…”
Section: Introductionmentioning
confidence: 99%